Plant growth shapes the effects of elevation on the content and variability of flavonoids in subalpine bilberry stands. (6th December 2020) - Filippi, A.; Braidot, E.; Petrussa, E.; Fabro, M.; Vuerich, M.; Boscutti, F.
Abstract: The study of morphological and physiological responses of shrubs to climate is crucial for the understanding of future scenarios regarding climate change. In this light, studying shrub growth and physiological acclimation along an elevation gradient might be insightful. The phenolic metabolic pathway represents a powerful tool to interpret such processes. In the South‐Eastern Alps, we investigated the relationships between elevation, plant traits ( i.e . age, xylem ring width, annual shoot length), plant–plant interaction ( i.e . shrub cover) and flavonoids in Vaccinium myrtillus L. (leaves, berries) in stands above the treeline. The relationships were parsed within causal networks using a confirmatory path analysis. Elevation was the main driver of V. myrtillus growth, having both direct and indirect effects on the leaf flavonoid content, but this was less evident for berries. In particular, the content of foliar flavonoids showed a peak at mid‐elevation and where the growth of xylem rings was intermediate, while it decreased in stands with higher shoot length. Flavonoid content variability of both leaves and berries was affected by elevation and shoot length. In berries, flavonoid variability was further related to all growth traits and shrub cover. These findings evidence that flavonoid content is influenced by both elevation and growth traits of V. myrtillus, often showing non‐linear relationships. These results suggest a trait‐mediated response of this plant to climate conditions as a result of trade‐offs between plant growth, plant defence, environmental stress and nutrient/resource availability. Abstract : Elevation is a major driver for the stimulation of plant flavonoid production in response to environmental stress, but the interplay of elevation with plant growth and plant‐plant interactions should never be neglected.